Producing electricity on board a ship in motion or stationary using photovoltaic panels - Popa, Nicolae-Silviu; Popescu, Mihai-Octavian; Mocanu, Vlad; Târhoacă, Mircea; Popa, Ciprian (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
A very important pillar for the world economy is the transport sector. Nowadays, about 80% of freight transport has been done by sea. Besides the recognized economic efficiency, ships are, unfortunately, an important sources of marine environment pollution. It is well known that the IMO is permanently concerned in maritime safety and many measures have been shown to be successful in reducing ship-sourced pollution. But it is not enough, new solutions must be found, and the answer can come from the direction of green energies (electricity produced from renewable sources). On board ships can be used as renewable energy sources wind energy or solar energy. Solar energy is easier to use because photovoltaic panels can be mounted on board the ship to produce electricity (however, provided that the photovoltaic panels do not increase the ship's forward resistance or reduce its manoeuvrability). Studies have shown that offshore wind energy is much more efficient than a ship-mounted wind turbine because an on-board wind turbine greatly reduces a ship's speed and manoeuvrability. The authors of the paper proposed to study the production of electrical energy obtained with the help of photovoltaic panels on board a ship in motion and stationary. The ship marched in the Mediterranean Sea for two months.